FORMULATION AND EVALUATION OF TRANSDERMAL FILMS CONTAINING CELECOXIB INCLUSIONS FOR TREATING PSORIATIC ARTHRITIS - J, MANASA; G, SAI KUMAR; IRIVENTI, PADMINI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective of the present work was to prepare and evaluate transdermal films and creams of celecoxib inclusions which are nonsteroidal anti-inflammatory drug to treat psoriatic arthritis. Methods: Celecoxib inclusions were prepared using β-cyclodextrin to increase the solubility. These inclusions were incorporated in transdermal films. Hydroxy Propyl Methyl Cellulose (HPMC), dibutyl phthalate, propylene glycol, and glycerin were used to prepare the film. Fourier transform infrared and differential scanning calorimetry studies were carried out for pure celecoxib and inclusions. Morphological properties, weight variation, surface pH, percentage elongation, folding endurance, in vitro disintegration, and in vitro diffusion studies were carried out for films. Results: All the results obtained were within the limits and confirmed the prolonged drug release and increased solubility of celecoxib inclusions. Conclusion: From the results obtained, increase in solubility of celecoxib drug was confirmed by forming inclusions using β-CD as polymer.